2022
DOI: 10.1002/hep.32417
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide meta‐analysis identifies susceptibility loci for autoimmune hepatitis type 1

Abstract: Background and Aims Autoimmune hepatitis (AIH) is a rare and chronic autoimmune liver disease. While genetic factors are believed to play a crucial role in the etiopathogenesis of AIH, our understanding of these genetic risk factors is still limited. In this study, we aimed to identify susceptibility loci to further understand the pathogenesis of this disease. Approach and Results We conducted a case–control association study of 1,622 Chinese patients with AIH type 1 and 10,466 population controls from two ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…Recently, in another Genome-Wide Association study of 1622 AIH-1 patients, Li et al confirmed the previous association of AIH with HLA, in this case, SNP RS6932730 located in the intronic region of the HLA-B gene, but also found associations with two novel loci, CD28-CTLA4-ICOS and SYNPR ( 29 ). Interestingly, CD28-CTLA4-ICOS is a co-stimulatory receptor gene cluster located on chromosome 2q33 that encodes both the positive (CD28 and ICOS) and negative (CTLA-4) T-cell regulators ( 29 ). Unfortunately, similar Genome-Wide Association studies have not been carried out in patients with AIH-2 since their numbers are much lower ( 28 ).…”
Section: Autoimmune Hepatitissupporting
confidence: 72%
“…Recently, in another Genome-Wide Association study of 1622 AIH-1 patients, Li et al confirmed the previous association of AIH with HLA, in this case, SNP RS6932730 located in the intronic region of the HLA-B gene, but also found associations with two novel loci, CD28-CTLA4-ICOS and SYNPR ( 29 ). Interestingly, CD28-CTLA4-ICOS is a co-stimulatory receptor gene cluster located on chromosome 2q33 that encodes both the positive (CD28 and ICOS) and negative (CTLA-4) T-cell regulators ( 29 ). Unfortunately, similar Genome-Wide Association studies have not been carried out in patients with AIH-2 since their numbers are much lower ( 28 ).…”
Section: Autoimmune Hepatitissupporting
confidence: 72%
“…The strong association of AIH-1 with HLA polymorphisms has been confirmed by the two genome-wide association studies (GWAS) performed so far in AIH, both including only AIH-1 adult patients ( 12 , 13 ). The first GWAS, carried out in a Northern European population, identified the class II HLA-DRB1*0301 as the allele with the strongest association with AIH-1, and HLA-DRB1*0401 as the second most strongly AIH-1- associated allele.…”
Section: The Human Leukocyte Antigenmentioning
confidence: 73%
“…The study also identified two non-HLA loci associated with AIH-1, i.e. the CD28-CTLA4-ICOS and the SYNPR loci, the first coding for proteins involved in T cell activation, and the latter coding for a protein expressed on synaptic membranes ( 13 ).…”
Section: The Human Leukocyte Antigenmentioning
confidence: 99%
“…In this edition of Hepatology , Li et al [ 3 ] report a genome‐wide meta‐analysis (GWMA) of type 1 AIH involving a total of 1622 cases and 10,466 population controls of Han Chinese descent. In this study, the authors confirmed association with the human leukocyte antigen (HLA) locus and identified genome‐wide significant ( p < 5 × 10 −8 ) association at two non‐HLA loci, harboring CD28 ‐ CTLA4 ‐ ICOS (at 2q33.3) and SYNPR (at 3p14.2), respectively.…”
Section: Figurementioning
confidence: 99%